Associations of Prenatal Exposure to Triclosan and Maternal Thyroid Hormone Levels: A Systematic Review and Meta-Analysis - Chen, Danrong; Liu, Jiani; Yan, Wu; Fang, Kacey; Xia, Yankai; Lv, Wei; Shi, Zhonghua (Frontiers in Endocrinology, 2021)
Objective: To quantitatively evaluate associations between exposure to triclosan during pregnancy and maternal thyroid hormone levels. Method: The databases of PubMed, Embase, Web of Science and Cochrane Library were systematically searched to identify relevant studies on the relationship between prenatal exposure to triclosan and maternal levels of serum thyroid hormone published before October 22, 2019. Stata 12.0 was used to examine the heterogeneity among the eligible studies. Results: Seven studies involving a total of 4136 participants were included. Overall, descriptive analysis provided no indication that exposure to TCS during pregnancy was related to either maternal FT4 levels (ES= 0.01, 95% CI: -0.03 – 0.05, P=0.00) or TSH levels (ES= -0.03, 95% CI: -0.13 – 0.07, P=0.412). Although the results were statistically insignificant, with the increase of urine TCS concentration, maternal FT4 levels exhibited a tendency to increase while TSH levels had a tendency to decrease during pregnancy. Conclusion: The results indicated that exposure to triclosan during pregnancy has no significant influence on maternal levels of thyroid hormone. On account of the inconsistency of existing research designs and study locations, further studies and replication are necessary to confirm these findings.